65 Sustainability of fish-derived feed inputs: an ecological perspective. (5th December 2019) - Tyedmers, Peter; Cashion, Tim; Parker, Robert
Abstract: Fishmeals and fish oils (FMFOs) sourced traditionally from directed fisheries and increasingly from seafood processing by-product streams, are important sources of key nutrients in animal diets. While attention is understandably paid to the relative nutritional attributes and prices of FMFOs, little consideration is typically paid to the resource utilization and environmental performance attributes of these products, beyond attending to the management status of source fisheries. This is somewhat surprising, however, given the diversity of species and ecosystems from which FMFOs are derived, their relative abundance, the technologies used in their capture, and energy sources used in their processing. Here, we present results of analyses of the greenhouse gas emission intensity (carbon footprint) and area of marine ecosystem to support the primary productivity required to sustain production of the species-specific biomass required (marine ecological footprint) to yield a tonne of fishmeal or oil for 18 distinct combinations of species, source ecosystem and fishing gear used to produce fishmeal and oil. Analyses of the carbon footprint of meals and oils included direct combustion and related upstream GHG emissions associated with direct fuel inputs to fishing along with emissions from processing-related fuel and electricity inputs. Analyses of the marine ecological footprint of meals and oils accounted for the trophic level of the source species as well as the source ecosystem-specific trophic transfer efficiency and average annual primary productivity. Results indicate that the carbon footprint of FMFOs varied by an order of magnitude while the marine ecological footprint of meals and oils varied by four orders of magnitude amongst the sources assessed. Given these substantial environmental and ecological performance differences between many widely traded FMFOs, there is substantial scope for feed formulators to construct and market low environmental impact feeds while maintaining nutritional and cost profiles.